EFEKTIVITAS OBAT KUMUR EKSTRAK ETANOL DAUN BELUNTAS (Pluchea indica L. ) UNTUK MENGATASI HALITOSIS PADA REMAJA - Ni Nengah Sumerti; Regina Tedjasulaksana; Maria Martina Nahak (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Known as bad breath, halitosis also called oral malodor is a bad breath that comes from air expelled by a person through the mouth. Halitosis is caused by local and systemic factors, but 90% of patients with halitosis due to local factors in the oral cavity, including at adolescents. The purpose of this study was to determine the effectiveness of mouthwashes of ethanol extract of leaves beluntas to overcome halitosis. This is an experimental research with completely randomized with pre-post control group design. Samples are adolescents junior high school students. Data were analyzed by Wilcoxon test, Results shown that there is a significance difference before and after rinsing in the groups and Friedman test shown that there is the significance difference between groups. The results of the study shown that mean average of mouth rinsing with ethanol extract of beluntas leaves with 12.5% in concentration is 0.167 ± 0.408, with p = 0.038 or p 0.05, rinsing with ethanol extract of beluntas leaves with 25% in concentration is 0.516 ± 0.408 , with p = 0.023 or p 0.05, mouth rinsing using chlorhexidine 0,12% shown that mean is 0.000 ± 0.000, with p = 0.020 or p 0.05. mouth rinsing using Base formula material shown that mean is 0,833 ± 0.408, with p = 0,157 or p 0.05. Analyze differences between groups to know the efectiveness of mouthwash treatment with Friedman test shown that p value = 0.000 or p0.05. The conclusion is rinsing with ethanol extract of beluntas leaves with 12.5% and 25% in concentration and chlorhexidine 0,12% can reduce halitosis significantly, but rinsing with base formula of mouthwash can not be overcome halitosis significantly. There are significant differences of effectiveness of mouthwash between groups to overcome halitosis. Keywords: mouthwash, ethanol extract of beluntas leaves, halitosis, adolescent